Volume Uncertainty in Construction Projects: A Real Options Approach - Ribeiro, João A. (2021)
This paper proposes a model aiming to quantify the impact that a specific type of uncertainty -volume uncertainty- may produce on construction projects’ value and on the optimal bid price, in the context of bidding competitions. Volume uncertainty is present in most construction projects since managers do not know, during the bid preparation stage, the exact volume of work that will be executed during the project’s life cycle. Volume uncertainty leads to profit uncertainty and hence the model integrates a discrete-time stochastic variable, designated as “additional value”, i.e., the value that does not directly derive from the execution of the tasks specified in the bid documents, and which can only be properly quantified by undertaking an incremental investment in human capital and technology. The model determines that, even only recurring to the skills of their own experienced staff, contractors will produce a more competitive bid provided that the expected amount for the additional profit is greater than zero. However, construction managers often need to hire specialized firms and highly skilled professionals in order to quantify the expected amount of additional value and, hence, the impact of such additional value inthe optimal bidding price. Based on the option to sign the contract and to perform the project by the selected bidder, identified and evaluated by Ribeiro et al. (2017), the model’s outcome is the threshold value for this incremental investment. A decision rule is then reached: construction managers should invest in human capital and technology provided that the cost of such incremental investment does not exceed the predetermined threshold value.